Identifying Agriculturists' Online Communication Tool Training Needs - Courtney Meyers; Kelsey Shaw; Erica Irlbeck; David Doerfert; Katie Abrams; Chris Morgan (Journal of Applied Communications, 2015)
Online communication tools, specifically social media, have provided new ways for agriculturists to promote and advocate for agriculture. Although agricultural producers find value in using social media to communicate about agriculture, many are not comfortable using these tools. The purpose of this study was to identify and prioritize training needs of agriculturists regarding use of various online communication tools. The USDA’s Beginning Farmers and Ranchers Development Program provided funding to develop workshops that would help agriculturists learn to use online communication tools effectively. Members of seven agricultural organizations in three states were sent a link to an online questionnaire, and 185 completed responses were analyzed for this study. Across all tasks, the highest means for perceived importance dealt with website tasks while Twitter and blogging tasks had the lowest means for perceived importance. Many of the tasks respondents were most competent completing were the beginning steps and they were least competent completing more complex uses of social media. Using the Borich needs assessment model, respondents indicated a greater need for training on topics related to websites, other online communication tasks, and Facebook. These results were used to develop a daylong online communications training workshop in each of the states.
Keywords: Social media; online communication; needs assessment; farmers; ranchers